Identification of Leishmania Isolates From Healing and Nonhealing Cutaneous Leishmaniasis Patients Using Internal Transcribed Spacer Region PCR - Tolouei, Sepideh (Kowsar, 2014)
BACKGROUND: Cutaneous Leishmaniasis (CL) is a parasitic disease in most parts of Iran, especially in the Isfahan province. The most common form of CL is a self-healing lesion but in rare situations, infection might develop to non-healing forms. Clinical symptoms and treatment process might be influenced by several agents such as host immune response and parasite strains. In this study, the isolates which caused healing and nonhealing forms of CL in Isfahan were characterized by internal transcribed spacer (ITS) polymerase chain reaction (PCR) technique. OBJECTIVES: The aim of this study was to identify Leishmania species isolated from healing and non-healing CLs using PCR method. PATIENTS AND METHODS: Thirty patients resident in Isfahan province, with healing or non-healing form of CL were entered into this study. After DNA extraction, the identification of Leishmania isolates was done by ITS1-PCR method. RESULTS: Leishmania major was found as the predominant species (100%) in both healing and non-healing forms of CL. CONCLUSIONS: It seems that there is no difference between Leishmania species in healing and non-healing forms of CL. In order to recognize the reason of long lasting lesions in non-healing patients, the study about parasite strains and immune factors at the molecular level mostly in nonhealing patient is recommended.